Regulation of the JAK/STAT signaling pathway in spinal cord injury: an updated review - Guo, Xinyu; Jiang, Chao; Chen, Zhe; Wang, Xiaohui; Hong, Fan; Hao, Dingjun (Frontiers in Immunology, 2023)
Cytokines are involved in neural homeostasis and pathological processes associated with neuroinflammation after spinal cord injury (SCI). The biological effect of cytokines, including those associated with acute or chronic SCI pathologies, are the result of receptor-mediated signaling through the Janus kinases (JAKs) as well as the signal transducers and activators of transcription (STAT) DNA-binding protein families. Although therapies targeting at cytokines have led to significant changes in the treatment of SCI, they present difficulties in various aspects for the direct use by patients themselves. Several small-molecule inhibitors of JAKs, which may affect multiple pro-inflammatory cytokine-dependent pathways, as well as STATs, are in clinical development for the treatment of SCI.This review describes the current understanding of the JAK-STAT signaling in neuroendocrine homeostasis and diseases, together with the rationale for targeting at this pathway for the treatment of SCI.